2017
DOI: 10.1016/j.fertnstert.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Neutral effect of body mass index on implantation rate after frozen-thawed blastocyst transfer

Abstract: Under highly controlled circumstances across 7 years of data from a single institution, using a uniform uterine preparation, following a precise transfer technique with high-quality day 5-6 slow frozen-thawed blastocysts, a BMI in the overweight range of 25-29.9 kg/m is not associated with a poorer implantation rate or live-birth rate, nor is it associated with an increased risk of miscarriage when compared with a normal BMI range. The increased length of time required during transfer for women with higher BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…Our results are consistent with a previous study performed based on the Latin American Registry that found no association between overweight and obesity and the likelihood of pregnancy, live birth, or miscarriage in women undergoing assisted reproductive technology [26]. Similarly, Insogna et al [27] reported no impact of BMI on implantation rates or clinical pregnancy rates in frozen-thawed blastocyst transfer. Nonetheless, the lack of statistical differences in our study could also be due to the possibility of type I statistical error.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with a previous study performed based on the Latin American Registry that found no association between overweight and obesity and the likelihood of pregnancy, live birth, or miscarriage in women undergoing assisted reproductive technology [26]. Similarly, Insogna et al [27] reported no impact of BMI on implantation rates or clinical pregnancy rates in frozen-thawed blastocyst transfer. Nonetheless, the lack of statistical differences in our study could also be due to the possibility of type I statistical error.…”
Section: Discussionsupporting
confidence: 93%
“…The blastocyst-stage slow-freeze cryopreservation, embryo thaw, controlled hormone replacement protocol and uterine preparation, and specifics of the embryo transfer itself are described in detail in a previously published report (9). Before blastocyst transfer, all women over the 7-year data collection period followed an identical preparatory protocol.…”
Section: Study Populationmentioning
confidence: 99%
“…A more recent study, including 461 women who underwent an identical freeze/thaw protocol with high-quality blastocysts transfer, was unable to find an association between BMI and the chance of implantation, pregnancy, or live birth. Nonetheless, this study was limited by a small sample size, with merely 59 women in the obesity group and 9 women in the underweight group [14]. Furthermore, inadequate selection criteria prevented it from drawing solid conclusions.…”
Section: Introductionmentioning
confidence: 99%